Echoing the Beats of Turbo-folk: Popular Music and Nationalism in ex-Yugoslavia - Slavková, Markéta (Lidé města, 2010)
This paper discusses the popular musical phenomenon in the region of former Yugoslavia known as “turbo-folk” – also referred to as “the music of the war.” In the late 1980s and early 1990s, “turbo-folk” partly emerged from a postmodern mix of more readily accessible modern technologies (turbo – techno-pop beat) and the desire for “retraditionalization” (folk). Therefore, it could be seen as part of the occurrence of “the invention of tradition” in the process of re-constructing a group’s identity. This peculiar synthesis of transformed tradition combined with modernity could also be traced back to the communist-led social engineering and rapid urbanization, which, in fact, led to mass “ruralization” of the cities in Yugoslavia at the time. Noticeably more than any other music genre, “turbo-folk” has closely been linked to the expansion of nationalism, in which it played an important role in spreading the nationalistic discourse and “satisfying” the emotions of the masses. I argue that “Turbo-folk,” as a “form of identity,” continues to be closely related to the broader socio-political trends in the former Yugoslav countries.